The Efficiency Analysis of Choices Involving Risk - Hanoch, G.; Levy, H. (Review of Economic Studies, 1969)
G. Hanoch, H. Levy; The Efficiency Analysis of Choices Involving Risk1, The Review of Economic Studies, Volume 36, Issue 3, 1 July 1969, Pages 335–346, htt